Irradiation-Induced Synthesis of Ag/ZnO Nanostructures as Surface-Enhanced Raman Scattering Sensors for Sensitive Detection of the Pesticide Acetamiprid - Po-Tuan Chen; Yu-Chun Lu; Sripansuang Tangsuwanjinda; Ren-Jei Chung; Rajalakshmi Sakthivel; Hsin-Ming Cheng (Sensors, 2022)
Detecting pesticides using techniques that involve simple fabrication methods and conducting the detection at very low levels are challenging. Herein, we report the detection of acetamiprid at the quadrillionth level using surface-enhanced Raman scattering (SERS). The SERS chip comprises Ag nanoparticles deposited on a tetrapod structure of ZnO coated onto indium tin oxide glass (denoted as Ag@ZnO-ITO). Controlled Ag decoration of ZnO occurs via irradiation-induced synthesis. The morphology of the surface plays a significant role in achieving an enhanced SERS performance for acetamiprid detection. 4,4′-Dipyridyl (DPY) is used to investigate synthesis conditions for the chip, leading to an optimal irradiation time of 60 min. Furthermore, the enhancement factor for acetamiprid on Ag@ZnO-ITO is higher than 107. These results demonstrate that SERS sensors have the potential for practical use in acetamiprid detection.